Socio-economic study of water ball vendors: A study in Butwal Sub-Metropolitan City, Rupandehi - Devkota, Chiranjivi (Kaladarpan कलादर्पण, 2024)
The present study aims to correlate the socioeconomic characteristics of street fulki vendors and their opportunities and challenges. The study followed a mixed method approach along with 38 vendors taken for rapid questionnaire survey and 5 in-depth interviews. The study was empirically based on Pani Puri vendors in Butwal sub-metropolitan city of Rupandehi district, Nepal. A total of 38 respondents were endorsed for a rapid questionnaire survey while there were five in-depth interviews to triangulate the findings. The study confirmed that the majority of vendors were male and from an economically active age. The business was established with a small investment however there were different motivations for initiating the business. The informal nature of economic transactions, lack of official registration, and professional training are found as the major challenges though the low investment, higher return, greater satisfaction and lower risk of loss are significant opportunities. The study recommends that food hygiene is an important concept to prevent food-borne illnesses and outbreaks which to be addressed while promoting the Pani Puri business in the long run. Moreover, government policies on quality food and hygiene can play an important role.